Prescribing pattern in Rheumatoid Arthritis patients in a tertiary care teaching hospital - Dutta, Shakti B.; Beg, Mirza A.; Bawa, Shalu; Kaur, Amanjot; Vishal, Subhash (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Rheumatoid arthritis (RA) is associated with joint deformity and significant health care related expenses. This disease affects approximately 1% of the adult population, the prevalence of RA in India is approximately 0.75% and increasing trend has been observed. Irrational prescribing is a common phenomenon around the globe. The drug utilization studies form an important tool for the assessment of rational or irrational prescribing and WHO drug use indicators. Thus keeping this in view the prescribing pattern analysis in RA patients was done. Methods: This prospective study was carried out by the department of pharmacology in medicine OPD of SGRRIM and HS, Dehradun for one year. A total of 450 RA diagnosed patients were included in the study. The diagnosis was made on the basis of clinical assessment and lab parameters as rheumatoid factor and anti-ccp. The collected prescriptions were analyzed by using WHO drug use indicators. Results: Total of 450 prescriptions was analyzed. 378 (84%) were females and 72 (16%) were males. Most commonly presenting age group was 31-60 years 276 (61.33%). Family history and RA factor was positive in 168 (37.33%) and 318 (70.67%) patients respectively. Anti-ccp was raised in 408 (90.67%) patients. The comorbid conditions were type-2 diabetes mellitus 72 (16%), hypertension 48 (10.67%), hypothyroidism 36 (8%) and other associated illness 54 (12%). Total of 1655 drugs were prescribed during the study period. The prescribed drugs were disease modifying anti-rheumatic drugs (DMARDs) 582 (35.18%), vitamin-D3 and calcium supplements 320 (19.34%), analgesics 311 (18.80%), antacids 204 (12.33%), others 238(14.38%). 437 (26.40%) fixed dose combinations (FDCs), 3.67 drugs per prescription, 1145 (69.18%) drugs by brand names and 1161 (70.15%) drugs from the National List of Essential Medicine (NLEM) 2015 were prescribed. Conclusions: Drug prescribing pattern depicts that most commonly prescribed were DMARDs, vitamin-D3 and calcium supplements and analgesics. Most of the drugs were prescribed from NLEM 2015.